Assessment of biogas-powered absorption cooling systems and biomass potential for sustainable rural development: A case study in Yenişehir, Turkiye - Kenan Saka; Mehmet F. Orhan (Case Studies in Thermal Engineering)
This study examines the performance of a small-scale, single-effect absorption cooling system powered by biogas, designed to address the dual needs for cooling and energy in rural areas. The study focuses on Yenişehir, where animal-based biogas facilities are absent, and cold storage capacity is insufficient to meet local agricultural demands. The system achieves a maximum Coefficient of Performance of 0.82 and an exergetic efficiency of 40.4 % under optimized conditions. Exergy destruction is minimized to 1.79 kW under elevated absorber and condenser temperatures. The minimum biogas mass flow rate required is 0.0007 kg/s, utilizing biogas with a 65 % methane content. To sustain a cooling load of 10 kW annually, 63 cattle are required for biogas production. Based on the local livestock population, up to 250 biogas-powered absorption cooling systems could be implemented in the region. This study provides a sustainable framework for integrating biogas-based cooling and cold storage solutions, addressing the energy and storage needs of small and medium-sized farms while contributing to rural economic development.